(untitled) (Письма в ЭЧАЯ, 2024)
A new electron gun was developed for the high-voltage electron cooling system of the NICA collider. This paper presents the results of the current density distribution variability tests of the new gun prototype. The tests were done with a wire profile monitor. Various methods of deriving current density distribution from the wire profile monitor measurements were implemented and tested. The comparison with theoretical prediction for profile variability revealed that our calculations accurately predict the shape of a beam with peak density at the center, but they underestimate the concavity of the profile of an electron beam with peak density on the edge